2022
DOI: 10.3390/jcm11154503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Serum Lipid Profile on the Risk of Breast Cancer: Systematic Review and Meta-Analysis of 1,628,871 Women

Abstract: Dyslipidemia has been linked to breast cancer incidence. The aim of the present meta-analysis was to further investigate the relationship between the serum lipid profile and breast cancer risk. Databases such as PubMed, EMBASE, and Web of Sciences were searched up to the end of January 2021 using certain MeSH and non-MeSH keywords and combinations to extract related published articles. Twenty-six prospective studies involving 1,628,871 women, of whom 36,590 were diagnosed with breast cancer during the follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…And was no important difference between laparoscopic hepatectomy and robotic hepatectomy in the length of stay, and also in the estimated blood loss. On the other hand, complications during surgery could lead to long operations and more blood loss and may raise the hospital stay because patients need more time to recover [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…And was no important difference between laparoscopic hepatectomy and robotic hepatectomy in the length of stay, and also in the estimated blood loss. On the other hand, complications during surgery could lead to long operations and more blood loss and may raise the hospital stay because patients need more time to recover [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 26 prospective studies involving 1,628,871 women showed that TG was significantly related to breast cancer development, and HDL-C was inversely related to breast cancer risk 46 . In the present study, the associations between these two biomarkers and OPS trajectory in the same direction as previous studies were observed only in premenopausal women, highlighting the importance of implementing strategies to improve lipid levels (increase HDL-C and reduce TG) before menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Dos Santos CR et al also disclosed that LDL-C signaling promoted BC cell survival and induced BC cell proliferation and invasion (15). In additon,the recent meta-analysis has highlighted the reversed correlation between HDL-C and BC occurrence (19). Experimental studies have also revealed that HDL-C contributes signi cantly in inhibiting the oxidative cascade of LDL-C oxidation and in alleviating in ammation stress, which may affect carcinogenesis (20,21).…”
Section: Discussionmentioning
confidence: 99%